PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DI DESA PAKRAMAN PADANGTEGAL KECAMATAN UBUD KABUPATEN GIANYAR - Juniartha, I Putu; Antara, Made; Sudarma, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 13 No 2 (2019)DO - 10.24843/EJES.2019.v13.i02.p08, 2019)
The results of this study indicate: (1) Characteristics of waste in Pakraman Padangtegal Village consisted of 83.88% organic waste, 7.24% plastic waste, 4.42% paper waste, 2.22% bottle waste, glass waste at 1.28% and metal waste at 0.96%; (2) public perception in waste management in Pakraman Village, Padangtegal that most of the people in Pakraman Village, Padangtegal, already know about the definition of waste and the danger of waste if it is not managed properly. Besides that the community also knows the difference between organic and inorganic waste so that the process of sorting waste in the place provided can run well, and the community's perception of waste management services has gone well with the transportation of waste twice a day; (3) the participation of the Pakraman Padangtegal Village community in waste management has played a role in various stages of waste management, starting from the sorting, garbage collection and garbage disposal, which complies with waste regulations and maintains the quality of the environment in Padangtegal Pakraman Village. The participation of the tourism industry in the process of waste management in Pakraman Village, Padangtegal, can be seen as being involved in the process of sorting waste and paying monthly fees and waste fees. The community participation in the waste management process is to help the government to socialize the waste management process by carrying out waste collection activities every week and provide a place for the waste management process. Suggestions in this study are that waste managers will immediately add facilities and infrastructure for waste transportation and accelerate the expansion of waste management in the village of Pakraman Padangtegal.   Keywords: Waste Management System, Pakraman Village